Visual representations in portuguese produced english language teaching coursebooks - Hurst, Nicolas Robert (Linguarum Arena, 2014)
This paper examines the role of illustrations in the context of English Language Teaching (ELT) coursebooks produced in Portugal. Taking illustrations to be one pilar in the construction of meaning through the representation of culture, the discussion shifts between their use over the last 35 years and their potential as a source of innovation and improvement in this area of ELT materials development. The central issue relates to the need for illustrations to perform something more than a decorative function in ELT coursebooks. Further discussion deals with the general issue of cultural content in language teaching materials, its importance in relation to situating language learning as both meaningful and purposeful. There are clear links themes related to foreign language teaching methodology (the learner-centred approach) and to curriculum development (citizenship education).It is argued that local coursebook publishers and writers should pay closer attention to the importance of cultural representation in language teaching materials, in this case to the use of illustrations, as a way of optimising the long-held influence of coursebooks as significant educational instruments.